Effect of daytime and nighttime on helicopter pilot’s gaze behavior: a preliminary study in real flight conditions - Chenyang Zhang; Jin He; Chuang Liu; Wenbing Zhu; Shihan Luo; Chaozhe Jiang (Aviation)
Nighttime affects pilot visual scan patterns and increase the risks of helicopter operations, contributing to many helicopter accidents and incidents. Several past studies have attempted to examine the effect of nighttime on helicopter pilot gaze behavior, but researchers had limited success due to the difficulty of collecting representative data under real flight conditions. The present study attempted to address this challenge by conducting a real flight study involving daytime and nighttime traffic pattern tasks and using a Tobii Glasses 3 eye-tracking device to collect helicopter pilot eye-tracking data. This study preliminarily explored the feasibility of data collection in real flight conditions in the context of eye-tracking research on civil helicopter pilots in China. Due to safety considerations, only one pilot was recruited to collect data in multiple tasks. Differences and correlations were examined for all gaze behavior metrics. The results suggested that pilot gaze behavior metrics and their correlations differed between daytime and nighttime flights in aspects critical to aviation safety. Pilot gaze behavior also varied with the flight phase. The findings from this study serve as a reference for optimizing helicopter pilot training systems, improving pilot performance during nighttime flights, and ensuring flight safety on helicopters.